To the question of the possibility of using laser irradiation of blood, as a method for the prevention and treatment of complications of coronavirus infection - L. I. Gusev; V. V. Safonov (Лечащий Врач, 2021)
The possibility of application of blood laser irradiation (BLI) in coronavirus infection was estimated, basing on the study whose purpose was prevention of chemotherapy complications in oncological patients by BLI method. The study showed that this method allows to increase immunity, enhances oxygen supply, relieves vasospasm, and prevents thrombus formation in the vessels. All these BLI features give a basis for use of this method in coronavirus infection.